The problem of piracy and the proliferation of counterfeit products in Ukraine: current state and prospects of avoiding it - Шуст, Наталія Борисівна; Корженівська, Тетяна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Counterfeiting and piracy are longstanding problems which are growing in scope and magnitude. They are of concern to governments because of the negative impact that they can have on innovation, the threat they pose to the welfare of consumers and the substantial resources that they channel to criminal networks, organised crime and other groups that disrupt and corrupt society. The article considers the problem of piracy and counterfeiting in Ukraine and offered possible options to avoid this problem. In the XXI century with the development of storage technologies, rapid reproduction and dissemination of information, particularly of copyright, very acute issue of developing effective measures to ensure adequate protection of objects against counterfeiting. Proper maintenance of effective legal protection of intellectual activity of misuse increasingly become the subject of research. The biggest threat for illegal distribution of counterfeit goods and copyright infringement is the Internet. Sharing of pirated content comprise more than one hundred thousand copies and illegal audiovisual programs. Home network (LAN) in Ukraine is also in demand among Internet users with the ability to access four different libraries of copyrighted works (movies, music, computer games, etc.). Widespread use of the Internet creates not only opportunities, but also a number of problems regarding effective protection and the protection of intellectual property rights. Piracy has deep character can not be overcome in some countries. But the international community and each country trying to develop an effective mechanism for simplified and accelerated copyright protection. The need for copyright protection is an urgent problem and present solution to this problem can only be close cooperation between copyright owners, government agencies and users, and use the experience of foreign countries. Because only orderly legal regulation, responsible attitude of the author to the distribution of their works and conscious attitude of users to copyright rights of others can negate all attempts copyright infringement. The issue of copyright protection on the Internet and means of combating offenses are complex. The main problem in this regard is that the regulatory framework of Ukraine lags far behind the realities of public relations in the field of intellectual property that results in unsettled areas of the law. That is why today before legislators and experts in intellectual property raises complex issues for improving and adapting the legal framework to protect copyright on the Internet.